Are Bryodrilus parvus Nurminen, 1970 and Bryodrilus librus (Nielsen and Christensen, 1959) (Annelida: Enchytraeidae) really different species? A revision based on DNA barcodes and morphological data - Dózsa-Farkas, Klára; Porco, David; Boros, Gergely (Zootaxa, 2012)
The taxonomic status of the enchytraeid species Bryodrilus parvus Nurminen, 1970 and Bryodrilus librus (Nielsen andChristensen, 1959) was tested with respect to their possible conspecifity. B. parvus, considered as a typical northern Hol-arctic species, was also found in Hungarian lowlands. The species B. librus (Nielsen and Christensen, 1959), distributedin Northern and Central Europe, is very close morphologically to B. parvus. In this paper we demonstrate that B. parvusand B.librus are not different species based on both morphological and molecular analyses of specimens from differentregions in Europe. The valid name of the species is Bryodrilus librus (Nielsen & Christensen, 1959) following the principle of priority (ICZN 1999, Art. 23.1).The species B. librus was revised and a new description is given here.